Brain death as a consequence of SARS-CoV-2 infection: An integrative review (Research, Society and Development, 2024)
Introduction: It is well known that coronaviruses (CoVs) generally exhibit neurotropic properties and, therefore, can result in neurological and neuropathic conditions. For this, there are several potential mechanisms, which can even cause brain death in the patient. Establishing brain damage of irreversible cause follows a protocol that may vary according to the country, usually consisting of two clinical examinations, an apnea test and a complementary examination. Thus, brain death has been reported in some studies in association with COVID-19. The objective of this review is to analyze the evidence on the correlation between COVID-19 infection and brain death. Methodology: This is an integrative literature review that used the PubMed and LiLaCS databases, from 2019 to 2023 to search for articles with the following descriptors: “Brain death; COVID-19; SARS-CoV-2” in Portuguese, English and Spanish. These terms were combined using the Boolean operators OR and three years of publication (from 2019 to 2023). Results and Discussion: Fourteen articles were selected for analysis in this work and among these, the main findings and associations between brain death and COVID-19 could be discussed according to the literature. Conclusion: Therefore, although brain death is present in many outcomes after infection by SARS-CoV-2, it is still not very prevalent and difficult to study, since patients evolve due to multiple causes, in an acute manner, making it impossible to perform more clinical and laboratory tests, requiring more studies on the subject.